Combined intranasal and intramuscular parainfluenza 5-, simian adenovirus ChAdOx1- and poxvirus MVA-vectored vaccines induce synergistically HIV-1-specific T cells in the mucosa - Beavis, Ashley C.; Wee, Edmund G. -T.; Akis Yildirim, Belkis M.; Borthwick, Nicola; He, Biao; Hanke, Tomáš (Frontiers in Immunology, 2023)
The primary goal of this work is to broaden and enhance the options for induction of protective CD8 + T cells against HIV-1 and respiratory pathogens. We explored the advantages of the parainfluenza virus 5 (PIV5) vector for delivery of pathogen-derived transgenes alone and in combination with the in-human potent regimen of simian adenovirus ChAdOx1 prime-poxvirus MVA boost delivering bivalent mosaic of HIV-1 conserved regions designated HIVconsvX. We showed in BALB/c mice that the PIV5 vector expressing the HIVconsvX immunogens could be readily incorporated with the other two vaccine modalities into a single regimen and that for specific vector combinations, mucosal CD8 + Tcell induction was enhanced synergistically by a combination of the intranasal and intramuscular routes of administration. Encouraging safety and immunogenicity data from phase 1 human trials of ChAdOx1-and MVA-vectored vaccines for HIV-1, and PIV5-vectored vaccines for SARS-CoV-2 and respiratory syncytial virus pave the way for combining these vectors for HIV-1 and other indications in humans.Effective HIV-1 vaccine is long overdue. Even on the landscape of preventive and therapeutic use of long-acting forms of antiretroviral medication combinations preventing AIDS and decreasing onward transmission of HIV-1, an effective HIV-1 vaccine will always be the best solution and likely a key component of any package truly ending the HIV-1/AIDS epidemic. While induction of broadly neutralizing antibodies (bNAbs) remains the primary focus of HIV-1 vaccinology, CD8 + T cells impose selective pressure on the virus and their protective potential should be harnessed by vaccines. Not all T cells are equally protective and a vaccine strategy for eliciting protective CD8 + T cells at key sites such as mucosa may serve as an important safety net against HIV-1 escape mutants breaking through the bNAb defense. Here, we outline some important principles for such an approach.